FE modeling of MEMS microphone performance - Wu, Yuxing. (2008)
The finite element method, ANSYS, was used to model and simulate the diaphragm. Both static and dynamic behaviors of corrugation diaphragm like mechanical sensitivity, natural frequency and deflection were analyzed using FEM. Circular, rectangular corrugated diaphragms were studied. Various factors that affect the performance like internal stress, corrugation depth, and diaphragm thickness were presented in Chapter 4.